2016
DOI: 10.1523/jneurosci.0492-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Homeostasis in the Direct Pathway in a Mouse Model of Asymptomatic Parkinson's Disease

Abstract: The characteristic slowness of movement in Parkinson's disease relates to an imbalance in the activity of striatal medium spiny neurons (MSNs) of the direct (dMSNs) and indirect (iMSNs) pathways. However, it is still unclear whether this imbalance emerges during the asymptomatic phase of the disease or if it correlates with symptom severity. Here, we have used in vivo juxtacellular recordings and transgenic mice showing MSN-type-specific expression of fluorescent proteins to examine striatal imbalance after le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 75 publications
7
50
1
Order By: Relevance
“…These observations confirmed and expanded previous reports in anaesthetized rodents (Mallet et al, 2006). The increased basal activity of iSPNs in vivo is attributed to their enhanced sensitivity to cortical inputs (Escande et al, 2016;Mallet et al, 2006;Ryan et al, 2018). In our slice study we observed an increase in AMPA-induced intracellular Ca 2+ responses specifically in iSPNs of lesioned mice, without change in dSPN.…”
Section: -Differential Changes In Intracellular Ca 2+ Transients In Ssupporting
confidence: 93%
“…These observations confirmed and expanded previous reports in anaesthetized rodents (Mallet et al, 2006). The increased basal activity of iSPNs in vivo is attributed to their enhanced sensitivity to cortical inputs (Escande et al, 2016;Mallet et al, 2006;Ryan et al, 2018). In our slice study we observed an increase in AMPA-induced intracellular Ca 2+ responses specifically in iSPNs of lesioned mice, without change in dSPN.…”
Section: -Differential Changes In Intracellular Ca 2+ Transients In Ssupporting
confidence: 93%
“…A 2A R is known to coexpress with D 2 R in the striatal iMSNs (Farrell et al, 2013; Oude Ophuis et al, 2014), so we used D 2 R promoter-driven eGFP-expressing mice (Escande et al, 2016) to investigate whether A 2A R activation and operant conditioning with the conditioned reward change iMSNs activities in the DMS (Fig. 5A).…”
Section: A 2a R Activation-induced Dms Imsns Excitation In Conditionementioning
confidence: 99%
“…In addition to these adaptations in intrinsic excitability, synaptic homeostatic plasticity is also engaged: iSPNs undergo substantial spine pruning in PD models [15*,1618]. However, unlike the situation in hippocampus, there is no obvious synaptic scaling; in fact, the strength of the remaining synapses is increased [15•,19,20]. This may be due, at least in part, to the fact that the loss of D2R signaling promotes LTP by dis-inhibiting A2a receptor (A2aR) signaling [21], which may disrupt scaling mechanisms.…”
Section: Introductionmentioning
confidence: 99%